Penyelenggaraan Pendidikan Berbasis Model Edutechnopreneur Islami - Siraj Siraj; Taufiq Taufiq; Ferri Safriwardy (Journal on Education, 2023)
Islamic character values should be the spirit that colors all aspects of education delivery, both in class-based learning, the climate of school life, and in the context of interaction with community life in general integrated into learning starting from planning, implementing, and evaluating in accordance with the characteristics of Basic Competencies (KD). Learning at SMK needs to be designed in accordance with the demands of the curriculum in an effort to instill islamic values through the practice of production-based training / production-based education and training learning and Islamic Edutechnopreneur. The purpose of this study is to describe the model of providing education based on the Islamic Edutechnopreneur model. This research uses a qualitative approach. The importance of this research is carried out because vocational and school teachers really need a model of providing education based on Islamic Edutechnopreneurs and their implementation in school life. The results showed that the success of the Edutechnopreneur production unit at SMK Negeri 7 Lhokseumawe really depends on the management implemented in the school. Therefore, it is important to strengthen the management of SMK so that the Islamic Edutechnopreneur production unit can be developed in an effort to strengthen the competitiveness of graduates. Teachers are an important resource, participating teachers in various trainings that allow them to develop in mastery of competencies and achieve increased insight and entrepreneurial skills.